2000
DOI: 10.1038/sj.onc.1203988
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of human papillomavirus E6 by protein kinase A: conditional degradation of human discs large protein by oncogenic E6

Abstract: The protein Kinase A (PKA) pathway was found to selectively regulate the function of oncogenic but not non-oncogenic E6 proteins. High risk E6 proteins are phosphorylated at their Dlg/PDZ binding motif at the C-terminus by a PKA like activity. This PKA and PDZ binding module is found only for human PV, is strictly conserved in all the transforming HPVs and is absent in all the low risk HPV types. We present evidence of a conditional regulation of E6 induced degradation of Dlg. HPV18E6 positive but not HPV nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 39 publications
4
64
0
Order By: Relevance
“…E6 phosphorylation by PKA reduces its capacity for binding and degrading Dlg. 22 It is possible that in the epithelial cells of SIL specimens E6 phosphorylation by PKA reduces its ability to bind Dlg and induce its degradation, explaining the high levels of Dlg observed in these samples. We investigated biopsies from other HPV-associated, intraepithelial, noninvasive pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E6 phosphorylation by PKA reduces its capacity for binding and degrading Dlg. 22 It is possible that in the epithelial cells of SIL specimens E6 phosphorylation by PKA reduces its ability to bind Dlg and induce its degradation, explaining the high levels of Dlg observed in these samples. We investigated biopsies from other HPV-associated, intraepithelial, noninvasive pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, this E6 function was specifically regulated by PKA phosphorylation of the E6 carboxy-terminal PDZ-binding motif. 22 E6 oncoproteins promote the degradation of other PDZ proteins, such as the human homologue of the Drosophila scribble oncosuppressor, h-scrib. 7 The ability of E6 to degrade 2 proteins with similar cellular functions emphasizes the relevance of these E6 activities to HPV-associated carcinogenesis.…”
mentioning
confidence: 99%
“…The PDZ domains are stretches of 80 -90 amino acids (Ponting and Phillips, 1995;Fanning and Anderson, 1999) that bind with high affinity to specific sequences (T/SXV) (Songyang et al, 1997), usually found in the extreme carboxy termini of their target proteins. The binding of certain of these sequences has been reported to be modified by phosphorylation (Ku¨hne et al, 2000;Tolkacheva et al, 2001;Choi et al, 2002) and it seems likely that this may be a more general mechanism for the temporal or spatial control of such protein interactions. PDZ binding motifs have been identified in a number of virus proteins that are associated with oncogenesis, including the HTLV-1 Tax protein, Adenovirus 9 E4-ORF1 protein and the E6 proteins of high-risk HPV types (Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The high risk HPV E6 proteins have been shown to be involved in de-regulating aspects of cell homeostasis related to cell growth and polarity in response to cell contact, through the degradation of hDlg (Gardiol et al, 1999;Ku¨hne et al, 2000;Pim et al, 2000; and MAGI-1 (Glaunsinger et al, 2000;Thomas et al, 2001). Given that MAGI-2 and MAGI-3 are highly homologous to MAGI-1, and that they are associated with such fundamental growth control pathways, it was obviously of interest to determine whether the high-risk HPV E6 proteins are able to interact with them.…”
Section: Introductionmentioning
confidence: 99%
“…For GST fusion protein production, HPV-16 E1, HPV-16 E2, HPV-16 E6, HPV-18 E6, HPV-18 E6*I, HPV-18 E6*I DM, HPV-16 E7 and Dlg fusion proteins were used as described previously Piccini et al, 1995;Massimi et al, 1996;Lee et al, 1997;Pim et al, 1997;Pim and Banks, 1999;Kuhne et al, 2000). GST-11 E2 was generated by cloning into pGEX-2T (BamHI/EcoRI) PCR products obtained by amplification with the following primers: 5 0 -AGCGGATCCATGGAAGCAATA-3 0 (F), 5 0 -AGC-GAATTCTTACAATAAATGTAATGA-3 0 (R).…”
Section: Plasmidsmentioning
confidence: 99%